Collaboration between veterinary services of cis countries - D. A. Lozovoy; A. M. Rakhmanov (Ветеринария сегодня)
The Article gives information on the meeting of CIS Intergovernmental Council for Collaboration in the Field of Veterinary Medicine which was held in Sochi, February 19-20, 2015. Different issues related to joint actions of the CIS Veterinary Services were discussed at the meeting.